Static and Dynamic Analysis of Linear Switched Reluctance Machine - Rafajdus, Pavol; Sekerak, Peter; Kalamen, Lukas; Hrabovcova, Valeria; Chen, Hao (Communications - Scientific letters of the University of Zilina, 2019)
This paper deals with the static and dynamic analysis of the Linear Switched Reluctance Machine (LSRM). The static parameters are investigated by means of Finite Element Method (FEM) for real LSRM and also for its optimized construction topology, where the air gap and mover dimensions are changed. The calculated static parameters are inputs into dynamic mathematical model of the LSRM. This model is simulated under Matlab/Simulink. The output values of the simulation are phase currents, voltages, flux linkages and total force in air gap of real and also optimized LSRM. The results comparison of the real and optimized LSRM is given.